Violating the law of one price: the role of non-conventional monetary policy - Stefano Corradin; Maria Rodriguez-Moreno (European Central Bank (ECB), 2016)
We document that a large yield spread, a basis, developed between USD- and EUR-denominated comparable bonds issued by the same euro area country over the 2008 – 2013 period. We find evidence that the basis varies over time, depending on liquidity withdrawn by strongly-constrained banks from the ECB and haircuts applied in the repo market, on the one hand, and the collateral policy and the liquidity supply conditions determined by the ECB, on the other. Overall, ECB collateral and liquidity factors explain a relevant share of the total variation in the basis and help to explain cross country dispersion in the basis.
Keywords: G01; G12; 330; financial frictions; law of one price; margin constraints; non-conventional monetary policy